Life table study of Sitotroga cerealella (Lepidoptera: Gelichiidae), a strain from West Africa - Hansen, L.S.; Skovgard, L.; Hell, K. (Oxford University Press, 2004)
Life table studies for the Angoumois grain moth, Sitotroga cerealella (Olivier), a pest on stored maize, Zea mays L., in West Africa, were conducted as part of the expansion of a mathematical simulation model that has been developed for two pests of stored maize. The effects of four temperatures (20, 25, 30, and 35°C) and two relative humidity levels (44 and 80%) on developmental time, age-specific survivorship and fecundity, sex ratio, and intrinsic rate of natural increase (rm) of S. cerealella were investigated. Sex ratio was close to 1:1 at all temperatures and humidity. Minimum development time occurred close to 32°C and 80% RH for both males and females, and developmental time of females was significantly shorter than that of males. Immature survivorship was highest between 25 and 30°C and 80% RH and lowest at 35°C under both humidity conditions. A similar low level was found at 20°C and 44% RH. The greatest fecundity (124 eggs per female) occurred at 20°C, 80% RH. The maximum rm value was 0.086 d−1 at 30°C and 80% RH, but the growth rate declined dramatically at 35°C. If compared with the few other life table studies conducted on this species on maize in India and North America, some variation among the strains becomes evident. A common conclusion for the current study and previous ones is that optimal population development for S. cerealella occurs at ≈30°C and at high humidity.